Cooling requirements of ball bearings lubricated by glass-fiber-filled polytetrafluoroethylene retainers in cold hydrogen gas - Coe, Harold H.; Scibbe, Herbert W.; Brewe, David E.; United States. National Aeronautics and Space Administration; Lewis Research Center (Washington, D.C. : National Aeronautics and Space Administration ; [Springfield, Va. : For sale by the Clearinghouse for Federal Scientific and Technical Information, 1970)
Experiments were performed with 40-mm-bore ball bearings operating at shaft speeds to 35 000 rpm and thrust loads to 400lbf (1780 N) in 60 degree R (33K) hydrogen gas. The minimum coolant flow rate equation developed for bearings equipped with this retainer material was similar to the equation determined in a previous study for bearings with a bronze-filled polytetrafluoroethylene (PTFE) retainer. Retainer wear rate was very low; some inner-race ball-track wear was evident for bearings that had been run for more than 7 hours.
Prepared at Lewis Research Center.
"February 1970."
Cover title.
Includes bibliographical references (p. 25).
Mode of access: Internet.
Keywords: Turbine pumps; Polytef; Glass fibers; Ball-bearings -- Lubrication; Hydrogen; Ball-bearings -- Cooling